The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/asia.201601741
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Organic Solar Cells Based on a Non‐Fullerene Acceptor with a Spiro Core

Abstract: Derived from perylenediimide (PDI) building blocks, 3D PDI molecules are considered as a type of promising structure to overcome molecular aggregation, thus improving the performance of organic solar cells. Herein, we report a novel PDI-based derivative, SCPDT-PDI , with four PDI units connected to a unique spiro core. Attributed to this novel molecular design, SCPDT-PDI exhibits a rigid 3D structure, in which the aggregation tendency of PDI chromophores could be effectively attenuated. Additionally, strong in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 39 publications
(173 reference statements)
0
21
0
Order By: Relevance
“…The ITO-coated glass substrates were washed and pretreated. 28,29 The precursor solution of ZnO was spin-coated onto the ITO glass and annealed (200 °C, 60 min). PTB7-Th:FSP blend solution was spin-coated on the ZnO layer to form the active layer (ca.150 nm) without any thermal or solvent annealing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ITO-coated glass substrates were washed and pretreated. 28,29 The precursor solution of ZnO was spin-coated onto the ITO glass and annealed (200 °C, 60 min). PTB7-Th:FSP blend solution was spin-coated on the ZnO layer to form the active layer (ca.150 nm) without any thermal or solvent annealing.…”
Section: Methodsmentioning
confidence: 99%
“…28 Our previous work showed that fullerene-free OSCs based on a 3D SM acceptor SCPDT-PDI 4 can reach a modest PCE of 7.11%. 29 SCPDT-PDI 4 is composed of a SCPDT spiro core and four PDI arms, in which two pairs of PDI units are conjugated with CPDT linker. The PDI units take a twisted conformation with a dihedral angle of 59 o relative to the CPDT core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to the Suzuki coupling, it is the most commonly utilized reaction to couple aromatic, in particular, thiophene-based cores with PBI units. It was used to prepare a plethora of aryl-bridged systems consisting of two or more PBI chromophores with linear, 141,142 spiro 143 or other twisted linkers.…”
Section: Replacement Of Halogen Atoms By Stille Sonoghasira and Glasmentioning
confidence: 99%
“…Currently, non-fullerene acceptor materials, including small molecules and polymers, have strong electron decient units such as naphthalene diimide (NDI), 12,13 perylene diimide (PDI), [14][15][16] diketopyrrolopyrrole (DPP), [17][18][19][20] or other building blocks with electron withdrawing moieties. [21][22][23] Small molecular acceptors are normally believed to be more superior than polymeric acceptors in terms of their purity and small batch to batch variance on synthesis, which is important for industrial scale applications.…”
mentioning
confidence: 99%